Assessment of healthy lifestyle habits among Mosul university students - Younis, Nasir (International Journal of Advanced Nursing Studies, 2014)
Background: A healthy lifestyle leaves you fit, energetic and at reduced risk for disease, based on the choices you make about your daily habits. Good nutrition, daily exercise and adequate sleep are the foundations for continuing good health. Managing stress in positive ways, instead of through smoking or drinking alcohol, reduces wear and tear on your body at the hormonal level. For a longer and more comfortable life, put together your plan for a healthy lifestyle and live up to it. Objectives: This study was aimed to assess of Healthy lifestyle habits among Mosul University Students and to examine relationship between the university student's characteristics and healthy lifestyles habits. Method: Cross-sectional survey design is applied to assess healthy lifestyle habit among Mosul University Students. Random sample consist of (400) students (Male and Female) were students in Mosul University from specialty difference (College of Medicine, College of Dentistry, College of Nursing, College of Pharmacy, College of Fine Arts, College of Education , College of Basic Education and College of Law),From end stage in University. Period of data collection first December 2013 extended from end February 2014. An interview technique method was used for data collection. Data were analyzed through the application of the descriptive and inferential statistical data analysis. Results: The results of the study indicated that Mosul university students have a low score in the total healthy lifestyle habits, demonstrating that female are higher than that of male(56%). Conclusion: The study concluded that the results are accepted concerning healthy lifestyle habit among Mosul University. After completing this survey, the researcher found that a lot of university students had a big problem of their healthy lifestyle habits, especially eating habits such as they skip breakfast, eat snacks and drink tea a lot. Keywords: Health, Lifestyle, Students, University.